2012
DOI: 10.1155/2012/575129
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Effects of Gap Junction Blockade on Neural Synchrony via a Motoneuron Network Computational Model

Abstract: In specific regions of the central nervous system (CNS), gap junctions have been shown to participate in neuronal synchrony. Amongst the CNS regions identified, some populations of brainstem motoneurons are known to be coupled by gap junctions. The application of various gap junction blockers to these motoneuron populations, however, has led to mixed results regarding their synchronous firing behavior, with some studies reporting a decrease in synchrony while others surprisingly find an increase in synchrony. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Consistent with these views, we found that larvae exposed to a low concentration of heptanol, a gap junction blocker (Saint-Amant and Drapeau, 2000, Muto and Kawakami, 2011, Warp et al., 2012), displayed neuronal avalanches with altered exponents and showed no evidence of self-similarity, presumably deviating the brain from a critical point. This suggests the involvement of gap junctions in maintaining criticality in the zebrafish brain, either due to gap-junction-specific synaptic properties or by affecting neuronal excitability and the E/I balance (Lewis and Rinzel, 2000, Traub et al., 2001, Memelli et al., 2012). Most probably, gap junctions are only a part of a functioning system that could settle at criticality due to a combination of multiple factors (synaptic plasticity, homeostasis, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these views, we found that larvae exposed to a low concentration of heptanol, a gap junction blocker (Saint-Amant and Drapeau, 2000, Muto and Kawakami, 2011, Warp et al., 2012), displayed neuronal avalanches with altered exponents and showed no evidence of self-similarity, presumably deviating the brain from a critical point. This suggests the involvement of gap junctions in maintaining criticality in the zebrafish brain, either due to gap-junction-specific synaptic properties or by affecting neuronal excitability and the E/I balance (Lewis and Rinzel, 2000, Traub et al., 2001, Memelli et al., 2012). Most probably, gap junctions are only a part of a functioning system that could settle at criticality due to a combination of multiple factors (synaptic plasticity, homeostasis, etc.)…”
Section: Discussionmentioning
confidence: 99%